The role of international Legislation and charters in the tourism industry - Asmaa mohammed Al Moqaram; Sumbul muhammed saki (Iraqi Journal of Architecture and Planning, 2018)
In many countries tourism industry considered a social and cultural phenomenon, in its role in changing work patterns and standards of living and income distribution. The success or fail of this industry depend on many environmental factors, natural (such as land, water, plants) and unnatural (man-made heritage buildings and historical cities).all this need different Interventions to create a magnet for tourists especially in valuable buildings. One of these are Legislation and conventions to manage and planning these environment. The research problem is the need to explore the Iraqi and international Legislations and conventions, by comparing between them we can identify the most appropriate and effective one that help to improve tourist industry and investment policy in heritage buildings and historical cities in Iraq. Therefore the aim of research is to clarify the most suitable local and international charters and Legislations for tourist investment policy in heritage buildings. This will be through identify the tourism industry concept and its criteria, and studying the most important characters like ICOMOS charters, finally drive findings and conclusions.Key words: tourism industry, historic building, heritage buildings, international Legislations and charters.